The effects of a standardized health education on the level of competency and perception of self-confidence in performing breast self-examination among adolescents, young adults, middle-age and elderly women of phase V, Sitio Lukban, Bagong Nayon, Antipolo Rizal - Reyes, Marina Lourdes M.
Education is a vital process in human growth and development. Progress and survival in a highly competitive world such ours require a more appropriate, relevant and realistic form of education in delivering important information to the public.Patient teaching is an integral part of patient care. The use of a standardized health education in patient teaching is the key to the success of innovative and preventive interventions such as breast self-examination (BSE).This study aimed to decrease cancer risk by early detection through the use of a standardized health education that will improve the accuracy in BSE practice. It emphasizes the nurse's role in assisting women with a very high risk of developing breast cancer. It recognizes perception of self-confidence as a critical factor in BSE performance.They study was community based. Cases were taken from a sub-urban community Phase V Sitio Lukban, Antipolo, Rizal. The sample consisted of 50 women. Data collection lasted from September to November 1991.The conceptual framework was based on the assumption that accuracy in BSE is dependent on the women's level of competency and perception of self-confidence in performing BSE as influenced by a standardized health education. Hypotheses used were organized according to the objectives and framework of the study. The variables studied included standardized health education, level of competency and perception of self-confidence, accuracy in BSE and demographic characteristics like age, marital status, education, and socio-economic status based on the monthly gross income of the head of the household. Instruments used in the study consisted of the observational checklists, forced-choice items questionnaires validated by on the spot home visits to the selected households of the respondents only one respondent was taken in each household.Statistical tests used to determine relationships and significant difference between or among the variables were percentage-ratio, paired t-tests, Pearson product moment correlation and analysis of variance (ANOVA).